Comparative Analysis of Satire and Sarcasm in the Criminal Comedy Show Lapor Pak Episode Pasukin Naik Gaji - Fadhiya, Nasywa; Otong Setiawan Djuharie (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study investigates the comparative use of satire and sarcasm in the criminal comedy show Lapor Pak! episode “Pasukin Naik Gaji.” Satire and sarcasm are both rhetorical devices used to criticize social realities through humor, but differ in subtlety and sharpness. The aim of this research is to identify and analyze the forms and meanings of satirical and sarcastic expressions in the show’s dialogues. This study uses a qualitative descriptive method and applies stylistic theory and humor theory as the analytical framework. The data source is a 26-minute episode aired on the 7Comedy YouTube channel on January 8, 2025. From the linguistic data collected, 20 utterances were found: 15 contain sarcasm, 11 irony, and 9 satire (some overlapping). The findings show that sarcasm is used more dominantly than satire, often reflecting economic frustration, while satire criticizes social issues in a more humorous and indirect way. Both styles serve not only to entertain but also to reflect social resistance and expose systemic injustice, especially regarding economic inequality. The analysis concludes that humor becomes a linguistic tool of social commentary and coping mechanism for workers.